Effects and moderators of exercise on muscle strength, muscle function and aerobic fitness in patients with cancer: a meta-analysis of individual patient data - Sweegers, Maike; Altenburg, Teatske M.; Brug, Johannes; May, Anne M.; Vulpen, Jonna K. van; Aaronson, Neil K.; Arbane, Gill; Bohus, Martin; Courneya, Kerry S.; Daley, Amanda J.; Galvao, Daniel A.; Garrod, Rachel; et al. (British journal of sports medicine, 2019)
Objective: To optimally target exercise interventions for patients with cancer, it is important to identify which patients benefit from which interventions. Design: We conducted an individual patient data meta-analysis to investigate demographic, clinical, intervention-related and exercise-related moderators of exercise intervention effects on physical fitness in patients with cancer. Data sources We identified relevant studies via systematic searches in electronic databases (PubMed, Embase, PsycINFO and CINAHL). Eligibility criteria We analysed data from 28 randomised controlled trials investigating the effects of exercise on upper body muscle strength (UBMS) and lower body muscle strength (LBMS), lower body muscle function (LBMF) and aerobic fitness in adult patients with cancer. Results: Exercise significantly improved UBMS (β=0.20, 95% Confidence Interval (CI) 0.14 to 0.26), LBMS (β=0.29, 95% CI 0.23 to 0.35), LBMF (β=0.16, 95% CI 0.08 to 0.24) and aerobic fitness (β=0.28, 95% CI 0.23 to 0.34), with larger effects for supervised interventions. Exercise effects on UBMS were larger during treatment, when supervised interventions included ≥3 sessions per week, when resistance exercises were included and when session duration was >60 min. Exercise effects on LBMS were larger for patients who were living alone, for supervised interventions including resistance exercise and when session duration was >60 min. Exercise effects on aerobic fitness were larger for younger patients and when supervised interventions included aerobic exercise. Conclusion: Exercise interventions during and following cancer treatment had small effects on UBMS, LBMS, LBMF and aerobic fitness. Demographic, intervention-related and exercise-related characteristics including age, marital status, intervention timing, delivery mode and frequency and type and time of exercise sessions moderated the exercise effect on UBMS, LBMS and aerobic fitness.
Online veröffentlicht: 4. September 2018
Gesehen am 02.09.2019